2014
DOI: 10.1371/journal.ppat.1004420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Uncultivable Bat Influenza Virus Using a Replicative Synthetic Virus

Abstract: Bats harbor many viruses, which are periodically transmitted to humans resulting in outbreaks of disease (e.g., Ebola, SARS-CoV). Recently, influenza virus-like sequences were identified in bats; however, the viruses could not be cultured. This discovery aroused great interest in understanding the evolutionary history and pandemic potential of bat-influenza. Using synthetic genomics, we were unable to rescue the wild type bat virus, but could rescue a modified bat-influenza virus that had the HA and NA coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 38 publications
(73 reference statements)
6
105
1
Order By: Relevance
“…None of the reassortants possessing any segment from H17N10 and the other seven segments from the parental virus PR8 were successfully rescued, as monitored by the production of replicative viruses in Madin-Darby canine kidney (MDCK) cells or chicken egg embryos. Considering the interaction between HA and NA and their importance for infecting cells, several attempts to rescue a reassortant with HA and NA from PR8 and the other six gene segments from H17N10 were unsuccessful, which is consistent with the results from previous studies (Juozapaitis et al, 2014;Zhou et al, 2014). We did not perform these experiments with HA and NA from H17N10 and the other six segments from PR8, considering that the receptors for H17N10 HA and NA are still unknown and that HA was unable to bind any known cell line Sun et al, 2013;Zhu et al, 2012Zhu et al, , 2013.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…None of the reassortants possessing any segment from H17N10 and the other seven segments from the parental virus PR8 were successfully rescued, as monitored by the production of replicative viruses in Madin-Darby canine kidney (MDCK) cells or chicken egg embryos. Considering the interaction between HA and NA and their importance for infecting cells, several attempts to rescue a reassortant with HA and NA from PR8 and the other six gene segments from H17N10 were unsuccessful, which is consistent with the results from previous studies (Juozapaitis et al, 2014;Zhou et al, 2014). We did not perform these experiments with HA and NA from H17N10 and the other six segments from PR8, considering that the receptors for H17N10 HA and NA are still unknown and that HA was unable to bind any known cell line Sun et al, 2013;Zhu et al, 2012Zhu et al, , 2013.…”
Section: Resultssupporting
confidence: 88%
“…They incorporated 95 nt from bat-H17 5¢ terminus with ATG mutated and 163 nt from bat-H17 3¢ terminus into the two terminals of the ORF of PR8 H1. A similar strategy was also applied to the ORF of PR8 N1 gene; that is, the PR8 N1 coding region was flanked by the 206 nt packing region sequence (with ATG mutated) from the 5¢ terminal of bat-N10 and 194 nt from the 3¢ terminal of bat-N10 (Zhou et al, 2014). Our work, together with the previous studies, partly demonstrated the importance of packing signals for virus rescue.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations